Event-triggered fault detection filter design for uncertain stochastic systems with package dropouts. (November 2019) - Ning, Zhaoke; Yu, Jinyong; Wang, Tong
In this article, the event-triggered fault detection filter design problem is concerned with uncertain stochastic systems subject to package dropouts. First, a filter structure is constructed to achieve the desired fault detection objective. Second, an integrated model with an event-triggered scheme and a Bernoulli stochastic process are employed to save the limited network resources and describe the package dropouts phenomenon, which always appears in the real network environment. A new sufficient condition is provided to ensure that the obtained residual system is mean square robustly exponentially stable and satisfies the desired detection performance. Then, a novel co-design algorithm is derived to obtain the parameters of filter and event-triggered scheme. Finally, two simulation examples are provided to verify the effectiveness of the proposed design scheme.